Reliable IPTV Service Delivery Using PIM-SSM Routing (Journal of Scientific Research, 2009)
Internet Protocol Television (IPTV) is a service where digital TV signal data is delivered by using Internet protocol (IP). Telecom and network operators focus on IPTV service for its fastest growth, lower price for operators and market economy. With the improvement of broadband connection and technology, IPTV will get more and more importance. Main challenge for IPTV service is resiliency and Quality of Service (QoS) to meet the users Service Level Agreement (SLA). The design space for IPTV service in terms of resilient backbone design, routing algorithms and fast failure restoration shall be explored. It is described from DSL FORUM and leading IPTV service-providing companies. In the context of this work, the PIM-SSM was configured and QoS was implemented for tagged VLAN of multicast traffic. IPTV traffic is analysed in ACREO testbed and Norrksen network.Keywords: IPTV; QoS; Multicast; PIM; PIM-SM; PIM-SSM; VLAN.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2633                 J. Sci. Res. 1 (3), 495-507 (2009)